Analysing language needs of the University of Limpopo business english students : an exploratory study - Meso, Thapelo Victor (My University, 2020)
Although the University of Limpopo (UL) students have been taught Business English (BE) for a number of years, their needs were never formally analysed. Hence, an exploratory research design was used to explore the needs of UL BE students, and a qualitative approached was followed. Thus, students and lecturers in Accounting and Financial Management were requested to fill in a questionnaire and to respond to interview questions, respectively, to identify students’ needs which were later analysed. However, Needs Analysis (NA) ought to be at the core of discipline-specific teaching and learning because it is learner-centred. This essential NA exercise is at the core of courses such as the UL BE one. Findings of this study indicate that students’ as well as content lecturers’ input is authentic and remain invaluable to BE courses as some of these mechanisms are vital for assisting lecturers fulfil students’ needs
Thesis (M. A.(English Studies)) -- University of Limpopo, 2020
Keywords: Language needs; Business English students; University of Limpopo; English language -- Business English